2015
DOI: 10.4161/21645515.2014.988549
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of co-purified acellular pertussis vaccines

Abstract: These authors contributed equally to this work.Keyword: Co-purified acellular pertussis vaccines, immune responses, protection, proteomic analysis Abbreviations: WPVs, whole-cell pertussis vaccines; APVs, acellular pertussis vaccines; PT, pertussis toxin; FHA, filamentous hemagglutinin; 2-DE, 2-dimensional gel electrophoresis; PRN, pertactin; FIM, fimbriae; BipA, putative outer membrane ligand binding protein; Sbp, sulfate-binding protein precursor; sphB1, autotransporter subtilisin-like protease; bvg, Bordete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
2
12
0
1
Order By: Relevance
“…B. pertussis strains in lineage V, the China endemic lineage, were estimated to start the divergence about 50 years ago (Figure 2). However, the lineage only accelerated the divergence with the emergence of sub-lineages Va, Vb, and Vc about 12 years ago (12 years for Va, 11 yrs for Vb and Vc, Figure 2), which occurred after the introduction and universal administration of ACVs in China (Figure 3) [22][23][24][25][26][27]. Consistent with previous studies, our result suggested that different lineages may have different mutation rates [10,13].…”
Section: Evolution Of Chinese Endemic B Pertussis Isolatessupporting
confidence: 88%
See 1 more Smart Citation
“…B. pertussis strains in lineage V, the China endemic lineage, were estimated to start the divergence about 50 years ago (Figure 2). However, the lineage only accelerated the divergence with the emergence of sub-lineages Va, Vb, and Vc about 12 years ago (12 years for Va, 11 yrs for Vb and Vc, Figure 2), which occurred after the introduction and universal administration of ACVs in China (Figure 3) [22][23][24][25][26][27]. Consistent with previous studies, our result suggested that different lineages may have different mutation rates [10,13].…”
Section: Evolution Of Chinese Endemic B Pertussis Isolatessupporting
confidence: 88%
“…ACVs could be produced with two different techniques: co-purification or separated purification. A few countries adopt co-purified ACVs (cp-ACVs) for the national immunization program, one of which is China [22]. In the cp-ACVs, individual antigen concentrations are not defined and the antigens are usually expressed as total protein nitrogen content [29].…”
Section: Discussionmentioning
confidence: 99%
“…The co-purified aPVs have more protein antigen than purified aPVs [14]. Therefore, this study further supported the hypothesis that the small antigen targets of purified aPV could induce the vaccine pressure and vaccine adaption more easily than the more antigen targets vaccine, such as wPV, even the co-purified aPV [15].…”
Section: Resultssupporting
confidence: 78%
“…In China, pertussis primary immunization using the whole cell pertussis vaccine (WPV) was introduced in the 1960s. Since 2013, the acellular pertussis vaccine (APV) had fully replaced the use of WPV throughout the country [ 25 ]. The immunization program recommended three doses of diphtheria, tetanus and acellular pertussis (DTaP) vaccine to be given at 3, 4 and 5 months of age and a booster dose given at 18–24 months of age.…”
Section: Discussionmentioning
confidence: 99%